2023
DOI: 10.3389/fimmu.2023.1128190
|View full text |Cite
|
Sign up to set email alerts
|

Cause or consequence? The role of IL-1 family cytokines and receptors in neuroinflammatory and neurodegenerative diseases

Abstract: Cytokines and receptors of the IL-1 family are key mediators in innate immune and inflammatory reactions in physiological defensive conditions, but are also significantly involved in immune-mediated inflammatory diseases. Here, we will address the role of cytokines of the IL-1 superfamily and their receptors in neuroinflammatory and neurodegenerative diseases, in particular Multiple Sclerosis and Alzheimer’s disease. Notably, several members of the IL-1 family are present in the brain as tissue-specific splice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 168 publications
0
1
0
Order By: Relevance
“…Data for C3AR1’s role in AD is limited, but a study in PS19 mice found that inactivation of C3AR1 was associated with decreased neuroinflammation and tau pathology ( Litvinchuk et al, 2018 ). IL-1β is a pro-inflammatory cytokine that drives neuroinflammation in AD but also has a protective effect on the CNS depending on the context ( Boraschi et al, 2023 ). These findings could be relevant to CAW’s underlying mechanisms but were specific to one sex and one mode of administration in each case, making it difficult to draw any strong conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Data for C3AR1’s role in AD is limited, but a study in PS19 mice found that inactivation of C3AR1 was associated with decreased neuroinflammation and tau pathology ( Litvinchuk et al, 2018 ). IL-1β is a pro-inflammatory cytokine that drives neuroinflammation in AD but also has a protective effect on the CNS depending on the context ( Boraschi et al, 2023 ). These findings could be relevant to CAW’s underlying mechanisms but were specific to one sex and one mode of administration in each case, making it difficult to draw any strong conclusions.…”
Section: Discussionmentioning
confidence: 99%